A novel Ni2MnCuSnAl0.1 multi-principal element alloy coating to enhance the wear resistance and corrosion resistance of Mg-Li alloy. (October 2021) - Wen, Xin; Cui, Xiufang; Jin, Guo; Jiao, Yunlei; Fang, Yongchao
Graphical abstract: Highlights: A multi-step ultrasonic assisted laser cladding for Mg-Li alloy was proposed. A metallurgical Ni2 MnCuSnAl0.1 MPEA coating was prepared on Mg-Li alloy. Typical gradient microstructure was obtained in Ni2 MnCuSnAl0.1 MPEA coating. The corrosion-resistance and wear-resistance of Mg-Li alloy were improved. Abstract: The evaporation and dilution of substrate are the key deficiencies that limit the performance of laser-cladded coatings on Mg-Li alloys (or Mg alloys). In order to overcome these drawbacks, in this work, a novel Ni2 MnCuSnAl0.1 multi-principal element alloy (MPEA) coating and a multi-step ultrasonic assisted laser cladding technique were proposed. Dense metallurgical Ni2 MnCuSnAl0.1 MPEA coatings were successfully synthesized on Mg-Li alloy. Typical gradient microstructure of low-diluted layer, diffusive layer and interfacial layer were obtained in the coating. The low-diluted layer was composed of BCC solid solution, Ni2 MnAl and Ni2 MnSn while the diffusive layer and interfacial layer showed an interactive microstructure of Mg-CuMg2 eutectic, Ni2 MnAl, Li2 MgSn/SnMg2 and Mg/Mg-Li substrate. The corrosion potential of Ni2 MnCuSnAl0.1 MPEA coating (-108 mVSHE ) was 1283 mVSHE higher than that of Mg-Li alloy (-1391 mVSHE ), while the corrosion current density of the coating (5.85 × 10 −7 A·cm −2 ) was about three orders of magnitude lower than that of Mg-Li alloy (1.12 × 10 −4 A·cm −2 ). The micro-hardness gradually increased from the substrate to the coating, and the average micro-hardness of the coating was 541.2 HV0.2, which is about 10 times higher than that of Mg-Li alloy ( 57.8 HV0.2 ). The wear resistance of Mg-Li alloy was also improved approximately 10 times by cladding Ni2 MnCuSnAl0.1 MPEA coating.